2021
DOI: 10.1097/yct.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm and Suicide Attempts Preceding and Following Electroconvulsive Therapy

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…10 A recent Danish population-based study that included more than 10,000 patients with unipolar depression, bipolar disorder, psychotic disorder, or personality disorder reported substantial significant reductions in the number of self-harm incidents and suicide attempts from the month preceding to the month following the initiation of ECT across all diagnostic groups. 11 Moreover, two recent large cohort studies revealed that ECT was associated with reductions in the risk of death by suicide in patients with depression. 12,13 However, data from the Danish National Patient Registry reported that ECT was associated with an increased risk of suicide in those with moderate depression, which most likely arose through bias by indication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A recent Danish population-based study that included more than 10,000 patients with unipolar depression, bipolar disorder, psychotic disorder, or personality disorder reported substantial significant reductions in the number of self-harm incidents and suicide attempts from the month preceding to the month following the initiation of ECT across all diagnostic groups. 11 Moreover, two recent large cohort studies revealed that ECT was associated with reductions in the risk of death by suicide in patients with depression. 12,13 However, data from the Danish National Patient Registry reported that ECT was associated with an increased risk of suicide in those with moderate depression, which most likely arose through bias by indication.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of a treatment course, 80% of patients with depression who reported experiencing suicidal thoughts and behaviors, defined as a score of 3 or 4 on the suicide item of the Hamilton Depression Rating Scale (HDRS), had a score of 0 10 . A recent Danish population‐based study that included more than 10,000 patients with unipolar depression, bipolar disorder, psychotic disorder, or personality disorder reported substantial significant reductions in the number of self‐harm incidents and suicide attempts from the month preceding to the month following the initiation of ECT across all diagnostic groups 11 …”
Section: Introductionmentioning
confidence: 99%
“…3 To the extent that cognitive adverse effects are a concern in a particular patient, Miller et al 4 found that high power in the electroencephalogram theta band predicts greater acute cognitive adverse effects from high-dose right unilateral ECT, thus creating an opportunity to monitor the ictal electroencephalogram and accordingly adjust the stimulus dose early in the treatment course. A rarer adverse effect of ECT is the occurrence of tardive seizure after the ECT session, and the impression of the rarity of this event is confirmed in this issue of the Journal by Warren et al 5 On a different note, although ECT is an acknowledged strategy to quiet suicidal ideation, [6][7][8][9] the corresponding literature on transcranial magnetic stimulation (TMS) and suicidal ideation has been sparse. Therefore, we welcome the randomized clinical trial by Hines et al 10 showing that intensive, thrice-daily TMS was superior to sham TMS in rapidly relieving acute suicidal ideation.…”
mentioning
confidence: 90%
“…The anti-suicidal effect of ECT across mental disorders is well-established [6][7][8][9][10][11][12][13][14][15][16]. However, because the "baseline" risk of suicide among patients receiving ECT is highly elevated, suicide remains a relatively common cause of death for those having received ECT [17][18][19].…”
Section: Introductionmentioning
confidence: 99%